MicroRNA-200a confers chemoresistance by antagonizing TP53INP1 and YAP1 in human breast cancer - Yu, San-Jian; Yang, Liu; Hong, Qi; Kuang, Xia-Ying; Di, Gen-Hong; Shao, Zhi-Ming (BMC cancer, 2018)
Emerging evidence suggests molecular and phenotypic association between treatment resistance and epithelial-mesenchymal transition (EMT) in cancer. Compared with the well-defined molecular events of miR-200a in EMT, the role of miR-200a in therapy resistance remains to be elucidated. Breast cancer cells transfected with mimic or inhibitor for miR-200a was assayed for chemoresistance in vitro. miR-200a expression was assessed by quantitative real-time PCR (qRT-PCR) in breast cancer patients treated with preoperative chemotherapy. Luciferase assays, cell proliferation assay were performed to identify the targets of miR-200a and the mechanism by which it promotes treatment resistance. Survival analysis was used to evaluate the prognosis value of miR-200a. In this study, our results showed ectopic expression of miR-200a promotes chemoresistance in breast cancer cell lines to several chemotherapeutic agents, whereas inhibition of miR-200a enhances gemcitabine chemosensitivity in resistance cancer cells. We found overexpression of miR-200a was closely associated with poor response to preoperative chemotherapy and poor prognosis in breast cancer patients. Furthermore, knockdown of YAP1 and TP53INP1 phenocopied the effects of miR-200a overexpression, and confirmed that TP53INP1 is a novel target of miR-200a. Remarkably, TP53INP1 expression is inversely correlated with miR-200a expression in Breast cancer cell lines. Taken together, these clinical and experimental results demonstrate that miR-200a is a determinant of chemoresistance of breast cancer. Upregulated miR-200a enhances treatment resistance via antagonizing TP53INP1 and YAP1 in breast cancer.